Naturen slår tilbage! - Andersen, Gregers (Tidsskrift for kulturforskning, 2014)
The article traces how anthropogenic climate change is often framed in the cultural imagination of the West as a phenomenon that will activate an animistic nature world. Through the medium of contemporary Western climate fiction (cli-fi) the article first shows how anthropogenic climate change is fictively configured as a phenomenon that triggers disasters that manifest themselves as the revenge of an intervening nature world. Intertwined by the thesis that these configurations point to a psychological desperation in a world in imminent need of an intervention that steer it away from impending ecological collapse the second part of the article focuses on contemporary philosophy and the work of Michel Serres and Bruno Latour. As especially Latour’s work is put through close reading the philosophies of both these thinkers are seen as another site, where the return of animism in contemporary disaster imagination reveals itself. This finally leads to a reflection on how anthropogenic climate change is intimately intertwined to a repertoire of cognitive schemes functioning as the narrative templates, through which this phenomenon is culturally imagined.